PERLINDUNGAN HUKUM KORBAN TINDAK PIDANA PERDAGANGAN MANUSIA (HUMAN TRAFFICKING) DALAM PERSPEKTIF PENEGAKAN HUKUM - Sukatma, Susandhi (NATIONAL JOURNAL of LAW, 2022)
Human trafficking, nowadays, is a problem that attracts the attention of thepublic, both nationally and internationally. Various efforts have been made toprevent the practice of human trafficking. Normatively, legal rules have beencreated to prevent and overcome human trafficking. However, human traffickingis still ongoing. Trafficking in persons is a form of crime against humanity.The purpose of this study is to analyze law enforcement against the crimeof human trafficking in Indonesia. And to analyze the legal protection of victims of human trafficking in Indonesia. The research method is a normative researchbecause specifically this research aims to provide an overview of the protection of victims of the crime of human trafficking in the perspective of Law no. 21 Year2007.The results of the study indicate that the birth of Law no. 21 of 2007concerning the Eradication of the Criminal Act of Trafficking in Persons is a formof law enforcement for the criminal act of trafficking in persons whose contentsinclude several things, namely: (1) the criminal act of trafficking in persons; (2)other criminal acts related to the crime of trafficking in persons; (3) investigation, prosecution and examination in court; (4) witness and victim protection; (5) prevention and treatment; and (6) international cooperation and communityparticipation. Protection of victims of criminal acts has 2 (two) meanings, namely: 1) legal protection not to become victims of criminal acts; 2) protection to obtain legal guarantees/compensation for the suffering/loss of people who have become victims of criminal acts.